2023
DOI: 10.1101/2023.01.16.524335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioregional boundaries and genomically-delineated stocks in snapper (Chrysophrys auratus) from southeastern Australia

Abstract: Marine species often exhibit genetic discontinuities concordant with biogeographic boundaries, frequently occurring due to changes in ocean circulation, bathymetry, coastline topography and temperature. Here we used 10,916 single nucleotide polymorphisms (SNPs) to assess the concordance between population genomic differentiation and coastal biogeography in the fishery important snapper (Chrysophrys auratus) across southeastern Australia. Additionally, we investigated whether spatial scales of assessment and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 96 publications
2
10
0
Order By: Relevance
“…This boundary coincides with species distribution limits, as well as population structuring for several species (Colgan, 2016), including an east-west divergence previously identified for A. butcheri and other sparids such as snapper, Chrysophrys auratus (Bertram et al, 2023;Burridge & Versace, 2006). The genetic differentiation present across Victorian locations is explained by the presence and convergence of strong ocean currents found across south-eastern Australia (i.e.…”
Section: Broad Scale Structuresupporting
confidence: 84%
“…This boundary coincides with species distribution limits, as well as population structuring for several species (Colgan, 2016), including an east-west divergence previously identified for A. butcheri and other sparids such as snapper, Chrysophrys auratus (Bertram et al, 2023;Burridge & Versace, 2006). The genetic differentiation present across Victorian locations is explained by the presence and convergence of strong ocean currents found across south-eastern Australia (i.e.…”
Section: Broad Scale Structuresupporting
confidence: 84%
“…Population genomic work has shown that the Australian locations selected in this study are represented by two geographically and genetically isolated snapper populations, known as the south-west (Bertram et al 2022) and the south-east (Bertram et al 2023) stocks. Muscle samples were obtained from 202 0+ aged YOY snapper recruits from the south-west stock (Cockburn Sound), as well as 202 YOY from the south-east stock (Port Phillip Bay; Table 1, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Here we utilized tissue samples taken from snapper belonging to two genetically distinct and geographically isolated stocks in southern Australia that were originally sampled for stock assessment purposes and for population genetic structure work (Conron et al 2020, Fairclough et al 2021, Bertram et al 2022, Bertram et al 2023). For the two stocks, both single-cohort YOY and adults of mixed ages were available for effective size estimation, allowing us to generate estimates of both N b in a single reproductive cycle and generational N e using the LD N e method.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike microsatellites, which are assumed to be selectively neutral, SNPs can be neutral or adaptive. Given that variation under local environmental selection may bias demographic inferences, we used datasets from which putatively adaptive variants had already been removed (as described in Barceló et al 2021, Bertram et al 2022, Pratt et al 2022, Bertram et al 2023. Based on these requirements, we identified suitable highquality datasets for five species (Figure 2, Table 1).…”
Section: Cataloguing and Integrating Existing Genetic And Genomic Dat...mentioning
confidence: 99%
“…Although these species provide only a snapshot of the diversity of connectivity patterns expected across our study region, they encompass both active dispersal strategies (bottlenose dolphins and common dolphins, herein 'active dispersers'), and advection-driven larval dispersal strategies (nerites, limpets, and snapper, herein 'larval' dispersers). Although snapper has a relatively long pelagic larval stage, our categorisation is an oversimplification because the species is also known to move during juvenile and/or adult stage (for details see Bertram et al 2022, Bertram et al 2023. Our study taxa include key species for MPA design in South Australia because of their priority status in conservation management plans and fishery stock assessments.…”
Section: Cataloguing and Integrating Existing Genetic And Genomic Dat...mentioning
confidence: 99%